The politics, economies, and ecologies of Indonesia’s third generation of social forestry: An introduction to the special section - Fisher, Micah R.; Dhiaulhaq, Ahmad; Sahide, Muhammad Alif K. (Forestry Faculty, Universitas Hasanuddin, 2019)
Although Indonesia is experiencing one of the most complex transformations of social forestry policy in the world, there is a need to step back and more closely examine the politics, ecologies, and economies that provide context for its implementation. This introduction offers a synthesis of the collection of special section submissions in Forest and Society. We begin by navigating the current social forestry moment by presenting a heuristic for identifying the discourses underpinning the rapid expansion in support of social forestry schemes. These perspectives are fragmented across four continuously contested discourses: community-first, legal-first, conservation-first, and development-first. We then contextualize the historical developments that brought social forestry into its current form by laying out a genealogy of its antecedents across three distinct generations. These three generations of social forestry are roughly aligned with the overall political changes that have taken place in Indonesia, each of which engaged in their own mechanisms for defining and administering social forestry. The first generation roughly follows the period of New Order rule; a second generation began as the regime unraveled, resulting in a period of reform and restructuring of the political system. At this time, new legal frameworks were introduced, followed by the development of new implementation mechanisms. We argue that social forestry has entered a third distinct period that is characterized by the expanding interests of numerous stakeholders to formalize permitting schemes. This third generation presents new possibilities for redefining land management on Indonesia’s vast national forests. The contributions to this special issue shed new light on the overall implications of these changes. We divide the findings across submissions, covering broad topical engagement on the economies, ecologies, and politics at different governing scales. From these findings we suggest a course for future research, and identify key policy challenges for the future of social forestry and for Indonesia.